2017
DOI: 10.1101/201277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein-protein interactions with fructose-1-kinase alter function of the centralEscherichia colitranscription regulator, Cra

Abstract: SummaryIn E. coli, the master transcription regulator Cra regulates >100 genes in central metabolism by binding upstream DNA operator sequences. Genes encoding glycolytic enzymes are repressed, whereas those for gluconeogenesis and the citric acid cycle are activated. Cra-DNA binding is allosterically diminished by binding to either fructose-1-phosphate (F-1-P, generated upon fructose import) or fructose-1,6-bisphosphate (F-1,6-BP). F-1,6-BP is generated from F-1-P by the enzyme fructose-1-kinase (FruK) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Strikingly, among 47 central metabolites F1P displayed the highest intracellular concentration variance across 23 different growth conditions and a highly significant direct correlation with FBP (Kochanowski et al, ), indicating that F1P is produced in E. coli also in conditions other than growth in fructose as the only carbon source. In this regard, a recent work described that the enzyme FruK can work reversibly and convert FBP into F1P (Singh et al, ). Interestingly enough, the same work reports that FruK interacts with Cra in vivo , and that conversion FBP into F1P regulates Cra/FruK affinity for Cra’s DNA operators in vitro (Singh et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, among 47 central metabolites F1P displayed the highest intracellular concentration variance across 23 different growth conditions and a highly significant direct correlation with FBP (Kochanowski et al, ), indicating that F1P is produced in E. coli also in conditions other than growth in fructose as the only carbon source. In this regard, a recent work described that the enzyme FruK can work reversibly and convert FBP into F1P (Singh et al, ). Interestingly enough, the same work reports that FruK interacts with Cra in vivo , and that conversion FBP into F1P regulates Cra/FruK affinity for Cra’s DNA operators in vitro (Singh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a recent work described that the enzyme FruK can work reversibly and convert FBP into F1P (Singh et al, ). Interestingly enough, the same work reports that FruK interacts with Cra in vivo , and that conversion FBP into F1P regulates Cra/FruK affinity for Cra’s DNA operators in vitro (Singh et al, ). Thus, these results raise an interesting scenario where, similarly to cAMP or fructose‐2,6‐bisphosphate (in mammals), F1P would act as a second messenger (that is, not involved directly in central metabolism) to relay metabolic fluxes into a physiological response, via regulation of Cra.…”
Section: Discussionmentioning
confidence: 99%
“…Since the homodimer is the minimal DNA binding unit for all characterized LacI/GalR proteins (reviewed in Reference ), we presumed that LLhF behaved accordingly. LLhF also binds the hetero‐protein FruK (Supplementary Methods, Table SI ), and this interaction was used as a model system for quantifying the interactions of a heteroprotein binding to a protein‐DNA complex with BLI.…”
Section: Resultsmentioning
confidence: 99%
“…Note that, as with the operator release experiments, the FruK binding assays did not discriminate whether the midpoint (a) corresponded to K d for FruK binding to the LLhF‐DNA complex or (b) was a composite of FruK binding and altered LLhF‐DNA binding in the presence of this heteroprotein. Interestingly, since FruK also binds to wild‐type FruR (the LLhF parent protein also known as “Cra”), this reasonably strong affinity indicates that FruK might play a physiological role in regulating central E. coli metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…The scenario could be indeed the case in view of the recent work of Kochanowski et al () indicating that that F1P can be produced in the absence of fructose as carbon source and that one can establish a correlation between F1P and FBP levels across different conditions. Along the line, it has been recently shown that F1P can be generated from FBP by FruK and that this enzyme interacts with Cra in vivo (Singh et al, ), an issue that deserves further research. It is clear that more studies are still necessary to interconnect all the possible actors and to establish under what conditions and in what way the Cra/F1P system manages to regulate the central metabolism.…”
Section: Introductionmentioning
confidence: 99%